Determination of Content and Oil Losses in Meal through Palm Kernel Pressing Process at PT XYZ Belawan - Simatupang, Dimas Frananta; Ginting, Maulidna; Agrifa, Utami Nanda; Sitinjak, Anna Angela; Simbolon, Merta (CHEESA: Chemical Engineering Research Articles, 2022)
PT XYZ Belawan has a kernel crushing plant unit that produces Crude Palm Kernel Oil (CPKO) with 700 tons/day capacity. Palm kernel processing is carried out in two pressing stages. The first stage or first press produces oil and cake, while the second stage or second press produces oil and meal. The meal still contains 7-8% of the oil content. This study is aimed to determine the amount of CPKO yield, oil content, and oil losses in a meal during the pressing palm kernel process. The method used was the calculation of the mass balance in each process flow. The mass balance calculation is carried out after collecting the secondary data from the factory, including the analysis of water content, solids, FFA, and oil content. Based on the calculation results, CPKO yield was 48.10% of the average kernel mass rate of 714.7155 tons and met the plant standard of at least 44%. Furthermore, the average yield of oil content from the meal was 7.45% and oil losses were 3.86%.